Theory of Planned Behavior Approach and Gender Differences on Students’ Intention to Practice Online Business - Suryawirawan, Okto Aditya (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2019)
The purpose of this study is to examine the influence of attitude, subjective norm, perceived behavioral control, gender and self-efficacy towards college students’ intention to practice online business in Surabaya. Theory of planned behavior is used to analyze student intention to become an entrepreneur through e-commerce especially online shop platform, thus becoming solution to decrease unemployment rate in Indonesia and furthermore increasing the economy of Indonesia in general. This research uses primary data resources which collected directly by distributing questionnaires to 114 respondents. The respondents are college students that use e-commerce application at least once a month. The findings of this study are attitude has a negative effect towards student’s intention to practice online business, subjective norm and perceived behavioral control have a positive effect towards student’s intention to practice online business. Self-efficacy could not moderate the effect of attitude on student’s intention to practice online business. Female college students have a higher intention to practice online business compared to male college students.